Influence of Roll Speed during Roll Compaction and Its Effect on the Prediction of Ribbon Solid Fraction - Martin Lück; Matthias De Saeger; Peter Kleinebudde (MDPI AG, 2022)
Influence of the roll speed (RS) during roll compaction on ribbon, granule, tablet properties and its effect on the prediction of the ribbon solid fraction at-gap is often neglected or controversially discussed. The aim of this study was to investigate the effect of the RS systematically. Microcrystalline cellulose (MCC) and lactose were compressed at several maximum roll pressures (<semantics>Pmax</semantics>) and RS combinations using a gap-controlled roll compactor. The ribbon solid fraction after elastic recovery (<semantics>SFribbon</semantics>), granule size distribution and tabletability of the granules as well as the ribbon solid fraction at-gap <semantics><mfenced>SFgap</mfenced></semantics> were measured. The Midoux number (Mi), derived from the Johanson model, was used to predict the ribbon solid fraction at-gap <semantics>(SFMi</semantics>). The measured <semantics>SFgap</semantics> and the predicted <semantics>SFMi</semantics> lead to a prediction accuracy (PA) of the Midoux number. The results are highly dependent on the material used and the applied <semantics>Pmax</semantics>. Higher plasticity of the material leads to a reduction in <semantics>SFribbon</semantics> and granule size with increasing RS. However, this effect can be overcome or reduced by adjusting <semantics>Pmax</semantics> above the yield pressure of the used material. These results allow for higher roll speeds as a potential upscaling method in roll compaction. On the other side, the PA of the Midoux number was also reduced with increased RS for MCC and had no effect for lactose. Thus, RS seems to be an important factor in the prediction of roll compaction processes and prediction models should include RS as a parameter to improve their accuracy.